1970
DOI: 10.1126/science.169.3947.762
|View full text |Cite
|
Sign up to set email alerts
|

Apollo 12 Magnetometer: Measurement of a Steady Magnetic Field on the Surface of the Moon

Abstract: The Apollo 12 magnetometer has measured a steady magnetic field of 36 +/- 5 gammas on the lunar surface. Surface gradient measurements and data from a lunar orbiting satellite indicate that this steady field is localized rather than global in its extent. These data suggest that the source is a large, magnetized body which acquired a field during an epoch in which the inducing field was much stronger than any that presently exists at the moon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…The Apollo missions shortly after, however, did detect small areas of weak crustal magnetic fields (Dyal et al 1970(Dyal et al , 1974Sharp et al 1973;Fuller 1974;Russell et al 1974). Recent high-resolution measurements characterized these LMAs to have size up to several hundred kilometers with surface magnetic field strengths ranging from 0.1 up to 1000 nT (Lin et al 1998;Mitchell et al 2008;Purucker 2008;Richmond & Hood 2008;Purucker & Nicholas 2010).…”
Section: Lunar Magnetic Anomalymentioning
confidence: 99%
“…The Apollo missions shortly after, however, did detect small areas of weak crustal magnetic fields (Dyal et al 1970(Dyal et al , 1974Sharp et al 1973;Fuller 1974;Russell et al 1974). Recent high-resolution measurements characterized these LMAs to have size up to several hundred kilometers with surface magnetic field strengths ranging from 0.1 up to 1000 nT (Lin et al 1998;Mitchell et al 2008;Purucker 2008;Richmond & Hood 2008;Purucker & Nicholas 2010).…”
Section: Lunar Magnetic Anomalymentioning
confidence: 99%
“…It does, however, have several small, static regions of low magnetic field ( -nT 50 500 ) on the surface (Dyal et al 1970;Coleman et al 1972). The distribution of these magnetic field anomalies on the Moon varies from thousands of kilometers across, irregular conglomerations and clusters, to relatively small (hundreds of kilometers across) and isolated featuressuch as the Reiner Gamma formation and Gerasimovich magnetic anomaly (Hood & Schubert 1980;Halekas et al 2001;Richmond et al 2003;Hood & Artemieva 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(Some of the interpretation of the early evidence for the presence of magnetised material in the samples was controversial, see Fuller 1974. ) However, direct evidence of the magnitude of the surface field was obtained through the use of the first lunar surface magnetometer delivered by Apollo 12 (Dyal et al 1970a). Using similar surface magnetometers on subsequent Apollo missions described by Dyal et al (1974) around the landing sites provided data that confirmed the existence of crustal magnetism.…”
Section: The Moonmentioning
confidence: 96%
“…The measurements start on 8 December 1969 at 13:38 UT. The large amplitude angular discontinuity at Explorer 35 at about 5 minutes after the start of the measurements caused a variation in the field measured by the LSM that is superposed on the steady ∼38 nT crustal field background (from Dyal et al 1972a) altitude of 100 km for a 10-months long operational phase, followed by a mission extension that came to an end on 11 June 2009 when the spacecraft was deorbited to impact the Moon. Kaguya carried a magnetometer that had been very carefully calibrated , and a long, 12-m magnetometer boom that was successfully deployed after launch.…”
Section: The Moonmentioning
confidence: 99%